Use of Chromogenic Agar Media for Identification of Uropathogen (Bangladesh Journal of Medical Microbiology, 2011)
Chromogenic agar media are increasingly being used as versatile tools in early differentiation and identification of Gram positive and Gram negative isolates from clinical specimens. We have evaluated the chromogenic medium as it’s use reduces the burden of biochemical characterization and reduces the workload for identification of bacteria. This study included 400 consecutively collected midstream and/or catheter-catch urine samples obtained from patients attending the hospital out patient department (OPD) and also from patients admitted in BSMMU hospital. They were inoculated on blood agar, MacConkey agar, cystine lactose, electrolyte deficient media and chromogenic agar plate for isolation of uropathogen. Out of 400 urine samples tested, 154 (38.5%) yielded significant growth of single organism and 16 (4%) yielded mixed growth. No growth was observed in 230 (57.5%) cases. The chromogenic agar media allowed the growth and primary identification in 171 (92.5%) strains out of 186 strains. The predominant uropathogens were Escherichia coli, Klebsiella spp. Enterococcus spp. and Eneterobacter spp. (KES group). The different coloured colonies produced by the breakdown of the chromogenic substrate by the specific enzymes of the bacteria were very useful in the presumptive identification of these organisms even from polymicrobial cultures by the color differences of the colonies. The medium also supported growth and differentiation of Gram positive organisms like Staphylococcus and Enterococci. Chromogenic agar media can be used as primary culture medium for isolation and identification of predominant uropathogens like E.coli, KES group and Enterococci. It is an easy to use primary screening medium that considerably reduces the daily workload and thus minimizes or limits the use of identification tests. Key words: Chromogenic agar medium, KES, CLED media, UTI DOI: http://dx.doi.org/10.3329/bjmm.v4i1.8464 BJMM 2011; 4(1): 18-23